Light Exposure during Days with Night, Outdoor, and Indoor Work. Issue 6 (13th March 2019) - Daugaard, Stine; Markvart, Jakob; Bonde, Jens Peter; Christoffersen, Jens; Garde, Anne Helene; Hansen, Åse Marie; Schlünssen, Vivi; Vestergaard, Jesper Medom; Vistisen, Helene Tilma; Kolstad, Henrik Albert
Abstract: Objective: To assess light exposure during days with indoor, outdoor, and night work and days off work. Methods: Light intensity was continuously recorded for 7 days across the year among indoor ( n = 170), outdoor ( n = 151), and night workers ( n = 188) in Denmark (55–56°N) equipped with a personal light recorder. White light intensity, duration above 80, 1000, and 2500 lux, and proportion of red, green, and blue light was depicted by time of the day and season for work days and days off work. Results: Indoor workers' average light exposure only intermittently exceeded 1000 lux during daytime working hours in summer and never in winter. During daytime working hours, most outdoor workers exceeded 2500 lux in summer and 1000 lux in winter. Night workers spent on average 10–50 min >80 lux when working night shifts. During days off work, indoor and night workers were exposed to higher light intensities than during work days and few differences were seen between indoor, outdoor, and night workers. The spectral composition of light was similar for indoor, outdoor, and night workers during days at and off work. Conclusion: The night workers of this study were during night hours on average exposed for a limited time to light intensities expected to suppress melatonin. The indoor workers were exposed to light levels during daylight hours that may reduce general well-being and mood, especially in winter. Outdoor workers were during summer daylight hours exposed to light levels comparable to those used for the treatment of depression.